Evaluasi Sistem Akuntansi Penerimaan KasvDalam Rangka Meningkatkan Pengendalian Intern Pada Pt. Luas Nusantara di Bojonegoro - Giri Harto Prasojo; Tjandra Wasesa; Diana Zuhro (Jurnal Mahasiswa Manajemen dan Akuntansi, 2025)
The rapid and rapid population growth has a very large influence on the community's need for housing. Where a house is a primary human need, because a house is a means of shelter, protection and rest. The house is also a place to share joys and sorrows and build a household for a family. This condition is utilized by development companies, to develop their business in terms of providing housing facilities for the community such as housing, apartments, condominiums, and so on. PT. Luas Nusantara is a private company engaged in the largest developer in Bojonegoro which has a strong foothold in the strategic Bojonegoro market and a good position, where in increasing its sales target it uses a credit sales strategy. So this is interesting to do research. The purpose of this study is to determine and evaluate the cash receipt system in order to create an efficient and effective internal control system implemented by PT. Luas Nusantara. The research used is a type of descriptive qualitative research, the purpose of using this method is to try to find a new form of knowledge, explain in detail, find methods for solving problems, study various processes and find forms of practical applications. From the evaluation conducted at PT. The Archipelago still has weaknesses in the receipt system, including the duplication of functions between the cash receipt section and the recording section, and the finance department officers have never been rotated. From what has been described above, it can be concluded that (1) in the cashier's function, the dual function as a biller is prohibited, so this function must be separated so that there is no misappropriation of accounts receivable (2) forms with printed letters must be ready to be used in the next project, so that in the process there is no misappropriation by related parties (3) finance department officers should always be rotated.